2013
DOI: 10.1177/0013916513493909
|View full text |Cite
|
Sign up to set email alerts
|

Shared Paths to the Lab

Abstract: Spatial layouts can significantly influence the formation and outcomes of social relationships. Physical proximity is thus essential to understanding the elemental building blocks of social networks, dyads. Situating relationships in space is instrumental to formulating better models of collaboration and information sharing in organizations and more robust theories of networks and their effects. We propose, develop, and test a concept, the functional zone, which effectively captures Festinger et al.’s classic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…The results of the MMNL model showed no significant relationships between contact person(s) characteristics and the location choice of ftf interactions. On the contrary, previous studies did show that people from different groups have different ftf interaction patterns (e.g., Wineman, Kabo, and Davis 2009;Kabo et al 2015). The findings might suggest that personal characteristics and ftf interaction characteristics might be more important indicators for choosing a specific location type than contact person(s) characteristics.…”
Section: Discussionmentioning
confidence: 71%
“…The results of the MMNL model showed no significant relationships between contact person(s) characteristics and the location choice of ftf interactions. On the contrary, previous studies did show that people from different groups have different ftf interaction patterns (e.g., Wineman, Kabo, and Davis 2009;Kabo et al 2015). The findings might suggest that personal characteristics and ftf interaction characteristics might be more important indicators for choosing a specific location type than contact person(s) characteristics.…”
Section: Discussionmentioning
confidence: 71%
“…These socio-organizational relationships manifest themselves both digitally and physically, though research continues to show that physical interactions are the cornerstone of collaboration and meaningful ties (Waber et al, 2014). Because of the importance of these physical exchanges, the design of the physical workspace-the commercial building-can have an impact on the nature and frequency of interactions among members of organizations (Sailer and McCulloh, 2012), which can be critical to the success of the organization (Kabo et al, 2015). However, learning the true social and organizational ties among workers, which would be helpful in designing and managing these spaces, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…In the domain of workspace and organizational theory, researchers have noted a strong relationship between office design/layout and occupant satisfaction and performance (Sailer, 2011;Sailer and McCulloh, 2012;Kabo et al, 2015). Recently, researchers have noted that the physical designs of buildings can have large impacts on different metrics related to productivity, such as communication, collaboration, creativity, and innovation (Sailer, 2011;Kabo et al, 2015). Using the language of space syntax (Bafna, 2003), researchers have defined metrics defined by physical layout and correlated them with occupant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different types of workspaces are required when comparing academics to commercial workers [29]. While open-plan office layouts with increasing path overlap seem to increase collaboration [30], concentration may improve in cellular offices due to enhanced privacy and less interruptions.…”
Section: Introductionmentioning
confidence: 99%